ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS GOOD CORPORATE GOVERNANCE (Perusahaan yang Terdaftar Dalam Laporan Indeks CGPI Tahun 2011-2013) (Students' Journal of Accounting and Banking, 2015)
This study aims to examine investment opportunities, concentration of ownership, leverage, asset composition, company size, profitability, to the quality of good corporate governance listed on the Indonesia Stock Exchange. The population in this study are 60 companies CGPI listed on the stock exchange Indonesia 2011-2013. Data were analyzed using multiple linear regression analysis. Results of the analysis showed that the variable investment opportunity negative, company size, profitability positif influence quality good corporate governance. While variable, concentration of ownership, leverage, asset composition does not influence quality good corporate governance.Keywords: Investment Opportunity, Concentration of Ownership, Leverage, Asset Composition, Company Size, Profitability, Good Corporate Governance